Evaluasi Peran Badan Pembentukan Peraturan Daerah Dewan Perwakilan Rakyat Daerah Provinsi Kalimantan Tengah Periode 2014-2019 Dalam Pembentukan Peraturan Daerah - Suriansyah Murhaini (Belom Bahadat, 2020)
In Central Kalimantan a total of 73 regional regulations (perda) issued by all Local Governments were canceled by the Ministry of Home Affairs (Kemendagri). The study was conducted with an empirical legal research method with observation and interview steps. Based on the results of the study found several factors that influence the Regional Regulatory Formation Board in the implementation of the legislative function of the Central Kalimantan DPRD, namely the absence of working time standards for the Establishment of the Central Kalimantan Regional Legislative Council and the absence of work guidelines set internally to carry out the duties and functions of the Central Kalimantan Regional Legislative Council formation body.